Bioactive Compound Analysis and Antioxidant Activity Test on Ethanol Extract of Gotu Kola Leaves (Centella Asiatica) with Different Solvent Concentrations - Harahap, Susilawati (Formosa Journal of Science and Technology, 2024)
Gotu kola (Centella Asiatica) contains the active ingredients alkaloids, saponins, tannins, flavonoids, steroids and triterpenoids. Three bioactive groups, namely triterpenoids, steroids and saponins, are antioxidants that are beneficial for the health of the human body. The aim of this research is to identify the phytochemical content, total flavonoid content and antioxidant activity in gotu kola (Centella Asiatica) leaves with different solvent concentrations. The type of research is Qualitative and Quantitative with an Experimental laboratory research design carried out at the Itkessu Pharmaceutical Laboratory. The results of the phytochemical screening identified that pegagan (Centella Asiatica) leaves were positive for containing alkaloids, flavonoids, steroids, triterpenoids and saponins at both solvent concentrations. The UV-Vis results showed that the total flavonoid content in gotu kola (Centella Asiatica) leaves was 31.6271 mg QE/Gr for 70% ethanol and 21.7821 mg QE/Gr for 96% ethanol, while the IC50 value was 53.2210 ppm for 70% ethanol and 61.7269 ppm for 96% ethanol.